2016
DOI: 10.1021/acs.jpcc.6b00717
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Identification of Ag-Terminated “Multilayer Silicene” Grown on Ag(111)

Abstract: The electronic structure of the outermost layer of “multilayer silicene” was investigated by metastable atom electron spectroscopy (MAES). It is usually difficult to elucidate the electronic structure of an ultrathin film grown on a solid substrate excluding the contribution from the substrate, especially such as “multilayer silicene” grown on a Ag(111) substrate. MAES used in this study thus provides a proper solution because the excitation source, He*­(23S) atom, cannot penetrate through the first layer. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
3
13
1
Order By: Relevance
“…The proposed Si-surface was arguably fabricated/can be prepared by epitaxial growth of Si thin film on metal substrate under low temperature condition in a controllable way to remove other competing phases, therefore the surface ferromagnetism could be experimentally accessible. However we note that the previous reports about "multilayer silicene" on Ag substrate with a comparable surface structures have not been unambiguously explained by the model studied here; adatom structures with silver (or other impurities) may account for the observed periodicity [26]. Moreover, the low stability may make the surface reactive to unintended surface contamination, which may easily destroy the fragile electronic structure.…”
Section: Introductioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The proposed Si-surface was arguably fabricated/can be prepared by epitaxial growth of Si thin film on metal substrate under low temperature condition in a controllable way to remove other competing phases, therefore the surface ferromagnetism could be experimentally accessible. However we note that the previous reports about "multilayer silicene" on Ag substrate with a comparable surface structures have not been unambiguously explained by the model studied here; adatom structures with silver (or other impurities) may account for the observed periodicity [26]. Moreover, the low stability may make the surface reactive to unintended surface contamination, which may easily destroy the fragile electronic structure.…”
Section: Introductioncontrasting
confidence: 64%
“…3 Recently, the Si(111) thin films with surface reconstruction have been successfully fabricated on silver substrates via molecular beam epitaxy (MBE) growth in a ultrahigh vacuum chamber [41,42]. Although the exact surface composition is yet under debate [26],…”
Section: (A)mentioning
confidence: 99%
“…In the following, 1 ML corresponds to the saturation of the and on Ag/Si(111) films in the 473K-623K temperature range, [32] and by our own experimental results: from Auger electron spectroscopy (AES) and optical reflectance measurements, we have shown that the optical response of thick (>10 layers) Si/Ag(111) films grown at growth T =473 K or 503 K was similar to the one of diamond-like bulk Si, and that Ag atoms were segregated at the surface during growth. [33] The ABC stacking of Si double planes, similar to the one of diamond-like Si has been also evidenced by STM, [34] whereas the Ag termination of the surface has been confirmed by core-level photoemission spectroscopy (XPS) measurements ( growth T =503 K), [35] angle-resolved photoemission spectroscopy (ARPES) measurements (473 K≤ growth T ≤543 K), [36] metastable atom electron spectroscopy ( growth T =500 K), [37] and by deuterium exposure of the surface leading to the formation of Ag 3D islands (450 K≤ growth T ≤550 K). [38] The exact structure and surface termination of the thin Si films is therefore still discussed.…”
mentioning
confidence: 75%
“…A lot of works attributed the √3 × √3 multilayer silicene to the silicon (111) islands covered by a monolayer of Ag atoms, which is the well‐known Si(111)√3 × √3‐Ag reconstruction . This opinion is based on their similar surface structures observed in STM image and low‐energy electron diffraction intensity, and transmission electron microscopy observations (TEM) for Si(111) patterns, and comparatively study of their electronic structures by STS and metastable atom electron spectroscopy . On the other hand, the existence of √3 × √3 silicene is supported by Dirac cones in ARPES measurements, QPI in STS results, and 1 × 1 atomic structure and Moiré pattern induced by rotation between adjacent layers .…”
Section: Resultsmentioning
confidence: 99%